Energy, environmental, and economic benefits of hydrogen-enriched biofuel using ammonium hydroxide in reactivity-controlled compression ignition engines - Krishnamoorthy Ramalingam; Muralidharan Kandasamy; Ganesan Subbiah; Suresh Vellaiyan; Yuvarajan Devarajan; Davannendran Chandran; Revathi Raviadaran (Results in Engineering)
The depletion of fossil fuels and the escalating environmental threats from emissions are driving the adoption of electric vehicles (EVs), particularly in developed nations. Despite their promise, EVs face limitations such as high manufacturing costs, e-waste generation, and the risk of electricity shortages. Hydrogen-based fuels are a viable alternative, but unresolved challenges, including hydrogen storage and safety, hinder their widespread use. This study explores an innovative solution by investigating hydrogen-enriched biofuels in reactivity-controlled compression ignition (RCCI) engines. The proposed approach utilizes ammonium hydroxide as a hydrogen carrier, combined with waste leather fat oil (WLFO) and 100 ppm cobalt chromite nanoparticles. Three fuel blends, containing 30 %, 35 %, and 40 % ammonium hydroxide, were tested under various operating conditions to evaluate their combustion performance and emission characteristics. Additionally, an economic analysis was conducted to assess the cost-effectiveness of the proposed fuel blends. The findings revealed that the 35 % ammonium hydroxide blend with 65 % WLFO achieved notable reductions in nitrogen oxides (9.2 %), hydrocarbons (27 %), and smoke (26 %) compared to diesel, while maintaining similar heat release rates, brake thermal efficiency, and brake-specific energy consumption. The economic analysis demonstrated that this blend could reduce fuel costs by approximately 25.6 %, offering a cost-effective and environmentally sustainable alternative to conventional fuels. This study presents a novel approach by integrating hydrogen-enriched biofuels with RCCI technology, addressing key limitations of current hydrogen and biodiesel solutions while advancing the development of cleaner and more economical fuel alternatives.